MINAT SISWA DALAM MENGIKUTI PEMBELAJARAN PENDIDIKAN JASMANI DI SMA NEGERI 2 KABANJAHE - Aser Paul Nainggolan; Rizki Bastanta B Manalu; Rut Alisia Br Ginting (JURNAL CURERE, 2023)
The purpose of this study was to analyze students' interest in participating in physical education learning at SMA Negeri 2 Kabanjahe, Karo Regency. This research is a quantitative descriptive study using survey methods. As for the respondents in this study, there were 32 students in class X SMA Negeri 2 Kabanjahe. To answer the research questions used a questionnaire instrument. While the data analysis technique used is frequency in the form of a percentage. The results showed that the interest of SMA Negeri 2 Kabanjahe students in participating in physical education learning was included in the high category of 22 students or 68.75%. Students' interest in participating in physical education learning at SMA Negeri 2 Kabanjahe is in the very high category of 3 students or 9.38%, while 5 students or 15.63%, low and very low are 1 student or 3.13% respectively. Intrinsic factors and extrinsic factors support students' interest in participating in physical education learning.